Influence of ankle joint position on angles and distances of the ankle mortise using intraoperative cone beam CT: A cadaveric study - Vetter, Sven Y.; Beisemann, Nils; Swartman, Benedict; Keil, Holger; Kirsch, Joachim; Grützner, Paul Alfred; Franke, Jochen (PLOS ONE, 2019)
Background The precise anatomical reduction of the ankle mortise is crucial for the clinical outcome in unstable syndesmotic injuries. Intraoperative cone beam computed tomography (CT), in addition to two-dimensional fluoroscopy, provides detailed information about the reduction and implant placement. The aim of this study was to analyze the influence of the joint position on the fibula position in the incisural notch and to determine the inter- and intraindividual anatomical differences in the intact ankle joints. Methods A total of 20 fresh-frozen lower legs disarticulated in the knee joint of 10 individuals were included. The measurements were performed using a cone beam CT. The distances and angles were measured in the standard imaging planes. The mean values of distances and angles were compared during the different joint positions: 10° dorsiflexion, 0° neutral position and 20° plantar flexion. Results The influence of the joint position was on average as follows: The anterior tibiofibular distance was 3.68 mm in 10° dorsiflexion, 3.66 mm (0° neutral position) and 3.59 mm (20° plantar flexion). The posterior tibiofibular distance measured 7.82mm, 7.76mm and 7.82mm. The rotation of the fibula measured ten millimeters proximal the joint line was 1.2°, 1.3° and 1.05°. The fibular rotation determined 4mm was 9.3°, 9.4° and 9.4°. On average, the following intraindividual variations were observed: superior tibiotalar clear space of 0.27mm and 0.15mm medial; and anterior tibiofibular distance of 0.42mm, 0.38mm posterior and 0.24mm in the incisural notch. The proximal angle of the fibular rotation was 0.2° and distal 0.4°. The interindividual variations of the angles and distances exceeded the intraindividual values partly by 3 to 4 fold. Conclusions Within the scope of this study neither the tibiofibular distance, nor the tibiofibular angle changed significantly through the different joint positions. The intraindividual differences were little while the interindividual variations of the parameters were distinctive.